2021
DOI: 10.1002/adma.202007885
|View full text |Cite
|
Sign up to set email alerts
|

Direct Integration of Strained‐Pt Catalysts into Proton‐Exchange‐Membrane Fuel Cells with Atomic Layer Deposition

Abstract: (2 of 10)www.advmat.de www.advancedsciencenews.com Comparing Rotating Disk Electrode and Membrane Electrode AssemblyCatalysts were deposited with ALD onto glassy carbon electrodes and carbon-loaded GDL, for catalytic performance evaluation under RDE and MEA, respectively. Acid-leaching conditions were tested to achieve reproducible results. When no pretreatment is applied in the RDE measurement, it is equivalent to pretreating the as-deposited electrode with strong acid (electrolyte pH = 1). Cobalt oxide quick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 84 publications
0
15
0
Order By: Relevance
“…Generally, the commonality of these approaches is to change the electronic structure of the atomic surface by adjusting or controlling the physical and chemical state of the catalyst surface, so as to simultaneously optimize the binding strength between different reaction intermediates (e.g., *H, *O, *OOH, and *OH) and active sites. Analogously, surface strain engineering has emerged as one of the most promising ways in precisely modulating the electronic configuration and altering binding energies toward adsorbates by the atomic‐scale structural deformation effects (lattice compressive or tensile strain) 15–26 . Recent studies have shown that the lattice strain can be maximized to tailor the d‐band orbital overlap and significantly alter the Gibbs adsorption/desorption free energy for reactive intermediates by modifying the distance between atoms, and thus efficiently stimulate the intrinsic activity of the catalyst in various electrochemical reactions (e.g., HER, OER, and ORR) 15–19,27–32 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Generally, the commonality of these approaches is to change the electronic structure of the atomic surface by adjusting or controlling the physical and chemical state of the catalyst surface, so as to simultaneously optimize the binding strength between different reaction intermediates (e.g., *H, *O, *OOH, and *OH) and active sites. Analogously, surface strain engineering has emerged as one of the most promising ways in precisely modulating the electronic configuration and altering binding energies toward adsorbates by the atomic‐scale structural deformation effects (lattice compressive or tensile strain) 15–26 . Recent studies have shown that the lattice strain can be maximized to tailor the d‐band orbital overlap and significantly alter the Gibbs adsorption/desorption free energy for reactive intermediates by modifying the distance between atoms, and thus efficiently stimulate the intrinsic activity of the catalyst in various electrochemical reactions (e.g., HER, OER, and ORR) 15–19,27–32 .…”
Section: Introductionmentioning
confidence: 99%
“…In order to design such an ideal reaction system, constructing core/shell nanostructure is an effective strategy, due to the lattice mismatch between core and shell interface easily induces compressive or tensile strain imposed by core material onto shell layer 20,21,27,40–45 . In addition, the strain degree can be well controlled by adjusting the thickness of shells or atomic composition to achieve the enhanced catalytic property 16,27,29,34,36,42,46 . Ruthenium‐based catalysts are the cheapest Pt group metals, and has been proved to be an excellent catalyst for the HER/OER, such as Ru clusters, 47 RuS x , 48 RuO 2 , 9,49 RuP x , 50,51 RuB x , 52 and so on.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations